2013
DOI: 10.1123/ijsnem.23.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chronic Sodium Bicarbonate Ingestion and Interval Training in Highly Trained Rowers

Abstract: Recent research has reported performance improvements after chronic NaHCO3 ingestion in conjunction with high-intensity interval training (HIT) in moderately trained athletes. The purpose of the current study was to determine the effects of altering plasma H+ concentration during HIT through NaHCO3 ingestion over 4 wk (2 HIT sessions/wk) in 12 Australian representative rowers (M ± SD; age 22 ± 3 yr, mass 76.4 ± 4.2 kg, VO(2peak) 65.50 ± 2.74 ml · kg(-1) · min(-1)). Baseline testing included a 2,000-m time tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…There is some evidence that bicarbonate supplementation during a period of high-intensity interval cycle ergometer training can enhance the mitochondrial adaptations taking place (Bishop et al, 2010) and can also improve performance (Edge et al, 2006). A more recent study involving well-trained rowers, however, did not find that bicarbonate supplementation during 4 weeks of high-intensity interval training provided any performance advantage over the placebo supplementation condition (Driller et al, 2013).…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 92%
“…There is some evidence that bicarbonate supplementation during a period of high-intensity interval cycle ergometer training can enhance the mitochondrial adaptations taking place (Bishop et al, 2010) and can also improve performance (Edge et al, 2006). A more recent study involving well-trained rowers, however, did not find that bicarbonate supplementation during 4 weeks of high-intensity interval training provided any performance advantage over the placebo supplementation condition (Driller et al, 2013).…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 92%
“…Despite this, the reported effects are equivocal, with several studies reporting no effect on exercise performance and capacity 3,4,5,6,7 . Inconsistencies in the performance outcomes of sodium bicarbonate supplementation studies can be partly attributed to differing dosing regimens 4 , gastrointestinal (GI) discomfort experienced by some participants 8 , exercise models insufficient to be limited by hydrogen cation (H + ) accumulation 5 and individual variation in the response to supplementation 9 .…”
Section: Introductionmentioning
confidence: 89%
“…One study used long-term NaHCO 3 ingestion and found that the group that consumed 400 mg of NaHCO 3 /kg body mass 1.5 and 0.5 h before interval training (6–12 × 2 min at 100% maximal oxygen uptake), three times per week over 8 weeks, had greater improvements in the lactate threshold and short-term endurance performance during high-intensity exercise (time to fatigue at 100% pre-training V O 2 peak intensity) compared with the placebo group that did the exact same training [84]. The findings were not reproduced in a study in well-trained rowers [85]. Although the rowers improved over a 4-week training period, the addition of long-term NaHCO 3 supplementation during the training period did not significantly enhance performance further.…”
Section: Nutritional Training: Specific Goals Require Specific Methodsmentioning
confidence: 99%